Co-management of electricity and groundwater: an assessment of Gujarat's Jyotirgram Scheme - Shah, Tushaar; Verma, Shilp (2008)
In September 2003, the government of Gujarat introduced the Jyotirgram Yojana to improve rural power supply. Two major changes have since taken place: (a) villages get 24 hour three-phase power supply for domestic use, in schools, hospitals, village industries, all subject to metered tariff; and (b) tubewell owners get eight hours/day of power but of full voltage and on a pre-announced schedule. It has, however, offered a mixed bag to medium and large farmers and hit marginal farmers and the landless. This article offers an assessment of the impact of Jyotirgram, and argues that with some refinements it presents a model that other states can follow with profit.